Diagnosing Burn Wounds Infection: The Practice Gap & Advances with MolecuLight Bacterial Imaging - Nawras Farhan; Steven Jeffery (Diagnostics, 2021)
Burn injuries constitute a critical economic burden on healthcare infrastructures worldwide. They are often associated with high mortality rates due to severe complications. Infection is the most common complication, highlighting the importance of prompt and precise diagnosis in order to prevent detrimental consequences and to optimize patient outcomes. Here we examine the current standard of care for diagnosing infection in both burn and chronic wounds followed by an investigation into the research surrounding a relatively new technique for bacterial detection, fluorescence imaging. With five years of published research on bacterial fluorescence imaging (MolecuLight i:X device), we have summarized and analysed the validity of the procedure and compared it to the current standard of care; clinical assessment and microbiological analysis. We highlight the benefits that could be obtained through the use of this technology as well as the limitations and the feasibility of incorporating this novel procedure into the standard of care.